Design, Synthesis, and Biological Evaluation of Novel 2H‐Pyran‐2‐one Derivatives as Potential HIV‐1 Reverse Transcriptase Inhibitors. Issue 1 (19th December 2014) - Defant, Andrea; Mancini, Ines; Tomazzolli, Rossella; Balzarini, Jan
<x xml:space="preserve">Abstract</x> In search for more effective drugs against HIV infection acting as non‐nucleoside reverse transcriptase inhibitors (NNRTIs), a series of new molecules with hybrid structures based on the natural product (+)‐calanolide A and the synthetic molecule α‐APA, known as potent and selective inhibitors of this enzyme, were selected by docking calculations. A convergent synthetic strategy gave 21 compounds with a 2H‐pyran‐2‐one structural unit and bearing isosteric modifications, which were tested against HIV‐infected CEM cell cultures. Only compound 6 (4‐((2‐(1H‐indol‐3‐yl)ethyl)amino)‐6‐methyl‐2H‐pyran‐2‐one) displayed inhibitory activity (EC50: 25–50 µM). However, it was associated with a relatively high cytostatic effect on human T lymphocyte (CEM) cell cultures, not easily predictable, neither by the chemical structure nor by the computational approach. Although this drug design has failed in selecting a novel scaffold for NNRTIs, the results have driven the interest towards new potential antitumor molecules showing activity against L1210 murine leukemia and HeLa cervix carcinoma cells, among which compound 21 (6‐methyl‐4‐((2‐(naphthalen‐1‐yl)ethyl)sulfonyl)‐2H‐pyran‐2‐one) was the most effective (IC50: 0.95 and 2.9 µM, respectively).